Review of Anisotropic 2D Materials: Controlled Growth, Optical Anisotropy Modulation, and Photonic Applications. Issue 12 (27th October 2021) - Li, Xu; Liu, Haiyang; Ke, Congming; Tang, Weiqing; Liu, Mengyu; Huang, Feihong; Wu, Yaping; Wu, Zhiming; Kang, Junyong
Abstract: Anisotropic 2D materials are promising building blocks for future photonic and optoelectronic devices due to their low structural symmetry and in‐plane optical anisotropy. This review systematically summarizes the crystalline structure, growth dynamics, optical anisotropy and their modulation strategies, and the corresponding photonic applications for emerging anisotropic 2D materials. First, the physical properties and crystalline structures of typical anisotropic 2D materials are briefly introduced. After that, special attention is paid to the growth mechanism of low‐symmetry lattices, where the competition between different growth modes determines the crystal morphologies. Then, the physical principles of anisotropic optical absorption, photoluminescence, Raman scattering, photodetection, and nonlinear response are discussed based on recent scientific advances. The discussion on the techniques to modify the intrinsic in‐plane anisotropy, along with the possibility of introducing optical anisotropy to the isotropic materials, add a new degree of freedom to the control over their optical properties. The review of application prospects also helps bridge the gap between the scientific exploration of novel anisotropic materials and the development of polarization‐sensitive photonic devices. The discussions in this review will push forward the scientific frontier in the crystalline growth and anisotropy control of anisotropic 2D materials. Abstract : The emerging low‐symmetry 2D materials houses intriguing optical anisotropy. By engaging a variety of modulation techniques, such as twist angle, dimension, and strain, such optical anisotropy can be flexibility tuned. This pioneering research have also paved ways to the development of various photonic and optoelectronic devices including polarization‐sensitive photodetectors, waveplates, and light sources.